Bee culture for profit - Reed, Nora May (My University, 1898)
Introduction: To anyone who intends to manage bees for profit, knowledge of their structural peculiarities and life history will aid greatly in determining more accurately what conditions are necessary to their greatest welfare. Such knowledge, however, will never take the place of an acquaintance with those conditions under which actual practice has shown that bees thrive, but it will form a good basis for an understanding of whatever practice has found best in the management of these industrious and profitable insects. It may also show in what ways practice may be improved. In its life history we trace the bee from the Branch Aethropoda, Class Henapoda, winged insects. This includes the family Apidae, or bee family, of which there are several marked types of genera, such as Apis, the hive bee, Bombus, the bumble bee; Hylocopa, the carpenter bee; Megachile, the leaf cutter, and many others. All of these are very interesting to study, and each fulfills a purpose in the economy of Nature; but in this paper only the first Apis, or the hive bee; can be considered. There is another, Melipona, the stingless honey bee of the American tropics, which has often been brought up with the expectation of realizing important practical results from it. So far this has proved a failure, their honey yield is small, not well ripened, and not easily harvested in good shape, as the honey cells are of dark wax, and arranged in irregular clumps, like those of our bumble bees.
Citation: Reed, Nora May. Bee culture for profit. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Bees; Knowledge; Honey; Theses; Manuscripts (documents)